2019
DOI: 10.25135/acg.oc.5619.02.1160
|View full text |Cite
|
Sign up to set email alerts
|

3-Acyl(aroyl)coumarins as synthon in heterocyclic synthesis

Abstract: This review presents a systematic and comprehensive survey of the chemical reactivity of 3-acyl(aroyl) coumarins. The target compounds are important intermediates for the synthesis of a variety of synthetically useful and novel heterocyclic systems with different ring sizes such as isoxazole, pyrazole, 3H-triazolium salts, pyrimidine, pyridine, quinolone, benzoxocin, benzoxonin and benzoxepin.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

0
1
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
3
2

Relationship

1
4

Authors

Journals

citations
Cited by 5 publications
(2 citation statements)
references
References 67 publications
0
1
0
Order By: Relevance
“…[ 56,57 ] In view of all these facts and because of the continuation of our paintings on the synthesis of latest heterocyclic derivatives. [ 58‐65 ] The present review showed a broad view of the anti‐microbial properties expressed by compounds having a coumarin nucleus.…”
Section: Introductionmentioning
confidence: 93%
“…[ 56,57 ] In view of all these facts and because of the continuation of our paintings on the synthesis of latest heterocyclic derivatives. [ 58‐65 ] The present review showed a broad view of the anti‐microbial properties expressed by compounds having a coumarin nucleus.…”
Section: Introductionmentioning
confidence: 93%
“…Information on the use of bis‐ [15] or monohydrazonoyl halides is described in reviews summarizing the results of studies using these halides. Fragmentary references to the use of some representatives of this series in synthetic schemes can also be found in individual chapters of collections, [16] thematic reviews [17–21] or microreviews [22–24] devoted to the analysis of problems in the preparation of other heterocycles, as well as in articles where the results of synthetic work are presented [25]…”
Section: Introductionmentioning
confidence: 99%